"Bouncing back" after the Deepwater Horizon oil spill. Issue 2 (3rd April 2017) - Grattan, Lynn M.; Brumback, Babette; Roberts, Sparkle M.; Buckingham-Howes, Stacy; Toben, Alexandra C.; Morris, Glenn
Abstract : Purpose: The psychological and behavioral consequences of the Deepwater Horizon oil spill disaster were among the most widespread, long term, and costly of all oil spill-related disasters. However, many people were resilient, and understanding the factors associated with resilience in the immediate aftermath of this disaster are needed to guide early interventions. The paper aims to discuss this issue. Design/methodology/approach: In total, 133 adults from the Northeast Gulf Coast participated in a study of mental health outcomes during the oil spill and one year later. Participants completed a battery of measures that assessed their basic demographics, income status, perceived environmental risk (i.e. characteristic way people think about and interpret environmental risks), self-reported resilience (i.e. ability to "bounce back" after a disaster), and mental health status. Findings: Results of univariate analyses indicated similar, elevated levels of mental health problems at both time points; however, environmental risk perception was higher one year post-spill than during the spill. In multivariate analyses, income stability, increased time, higher self-reported resilience, and lower environmental risk perception were associated with better mental health outcomes while age and gender had no association. Originality/value: Oil spills are protracted disasters, and better mental health outcomes are linked to financial stability, as well as a belief in environmental restoration and one's own capacity for resilience. Since resilience and environmental worry are potentially modifiable processes, they might be targeted in prevention and early intervention efforts in order to create more robust, prepared individuals in the face of an oil spill disaster.